Кошкин дом: русская народная сказка : [0+] / оформ. ООО "Форпост" (Читаем детям, 2013)
Экземпляры: ФО-2 (20140129) / Инвентарный номер: 1 / Цена: 35.00 / Авт.знак: К 76 / ГРНТИ: 17.82 / ББК: 84(2Рос-Рус)6